Fulfillment of Citizens' Constitutional Rights In the Perspective of BPJS Kesehatan Services - Thalib, Wahyu A; B, Sumiyati; Djafar, Marwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to examine the fulfillment of citizens' constitutional rights in obtaining health services through BPJS Kesehatan membership and identify what factors hinder the health services of BPJS Kesehatan participants. Using an empirical juridical research method that focuses on the implementation of Law Number 24 of 2011 concerning BPJS and Law Number 17 of 2023 concerning Health. The main data used questionnaire, interview and observation data. The results of the study concluded that the fulfillment of citizens' constitutional rights in the health sector, such as promotive, preventive and curative efforts, has been carried out in accordance with existing regulations. Limited facilities and community conditions are an inhibiting factor. Suggestions in the research, so that BPJS Kesehatan can optimize BPJS Mobile services and educate the public to register for BPJS Kesehatan Online. Further research is suggested to analyze the empirical juridical aspects related to the effectiveness of mobile BPJS services for rural communities.